Pemberdayaan Masyarakat dalam Pelestarian Tradisi Baritan Jumat Kliwon Sebagai Warisan Budaya di Desa Laban - Alvina Dwi Damayanti; Difa Armelisa; Faridatul Bahriyah; Muhamad Ichrom; Palma Putri AK; Syafruddin Saan Al Anisi; Syifa Eryanna; Zulfa Maulidina Rosyar (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
The "Baritan" tradition in Laban Village is a form of local wisdom passed down from generation to generation by the Javanese people. This tradition is carried out as an expression of gratitude for the harvest and as an effort to prevent bad things through collective prayer. This research uses a qualitative approach with the Participatory Action Research (PAR) method, which involves participatory observation, interviews, and focus group discussions (FGD). The research results show that Baritan has strong cultural values, togetherness, mutual cooperation, religion and tolerance. This tradition also strengthens the social and spiritual bonds of society. Despite challenges from outsiders who consider it mystical, Baritan remains an important tradition that plays a role in maintaining local cultural solidarity and identity. In conclusion, Baritan is a significant cultural heritage in forming a harmonious relationship between society, nature and the spiritual life of Laban Village residents.